Elitzur-Vaidmanova bomba - Šraml, Matevž (Matrika, 2015)
This article presents the Elitzur-Vaidman bomb-testing problem. We imagine a large group of imaginary bombs, which have a light sensor. If it is hit by a photon it sets off the bomb. Some bombs are defective. We are trying to find out which one still work without setting them off. Firstly, we describe Mach-Zehnder interferometer and the basic design for interaction-free measurement, with which we successfully recognize 1/3 of the working bombs. Then we improve the efficiency of our measurements by introducing the Zeno effect. Finally, we look at the interaction-free "imaging" experiment and interpret the results.
Keywords: brezdimenzijsko slikanje; Elitzur-Vaidman bomb tester; Elitzur-Vaidmanove bombe; interaction-free imaging; kvantna optika; Mach-Zehnder interferometer; Mach-Zehnderjev interferometer; quantum optics